Agrarian distress: strategies to protect vulnerable sections - Vyas, V.S. (2004)
Present policies and programmes neither protect a sizeable section of the agricultural population from natural and market-induced uncertainities nor enable them to contribute meaningfully to overall growth of the economy. It is possible, however, to turn the tide by enhancing investment to strengthen the resource base of agriculture, devising suitable instruments to compensate small and marginal producers for losses from natural calamities, designing organisational interventions to impart strength to their economy, lightening the interest burden from non-formal sources of credit, and encouraging rural financial institutions to take over the debts of the farmers from usurious sources. A positive feature in our situation is that we have some examples of success in all these areas. There is a need to extend and scale up these efforts. - Reproduced.
Keywords: Agro industry; Rural economy; Agricultural economics; Agricultural policy; Agriculture; Agrarian structure